Optimization Of Conditions For Production Of Keratinase By Aspergillus Flavus By Submerged Fermnetation - MINI.K.D; MINI PAUL; JYOTHIS MATHEW (International Journal of Pharma and Bio Sciences, 2015)
The fungal strains were isolated from the soil samples collected from different localities in Ernakulam and Thrissur districts. The keratinolytic nature of the fungus made it easy to isolate using Vanbreuseghem’s hair baiting technique. The fungi collected were cultured in keratin agar medium. The keratinolytic nature of the fungi were noted by observing the zone of clearance in the keratin agar medium. In this study, out of 350 fungi isolated, 42 presented clear zones in the keratin agar media. The selected fungi were tested for enzyme production by submerged fermentation using keratin substrate. The highest production of extracellular keratinase was shown by the fungus identified as Aspergillusflavus Optimization of conditions like incubation period, temperature, pH, supplementary sources etc. for maximum production of enzyme by Aspergillusflavus was done. The maximum production of the enzyme was obtained ,at 6thday of incubation. The maximum enzyme production by the fungus A. flavus S125 was observed at 55°C and pH 9. In the study A. Flavus cultured on a simple medium supplemented with chicken feather, produced a protease mixture with high keratinolytic activity at high pH, and was very effective in feather degradation, suggesting its potential use in biotechnological processes involving keratin hydrolysis. Moreover, the serine-type keratinase produced by the strain was active over a wide range of pH and temperature.